Professional pathway for civil aviation authority of Malaysia (CAAM) aircraft maintenance license holder registered at BEM - Liew, Chee Leong; Abu Talib, Abd Rahim; Indiran, Viji (Airiti, 2020)
This paper proposes a professional pathway for Civil Aviation Authority of Malaysia (CAAM) Aircraft Maintenance License Holder (AML) currently registered with the Board of Engineers Malaysia (BEM). It carries out a study on how the professional pathway enhances the AML holder professional development and complement CAAM functions. It highlights the importance of professional development and the importance of compliance of code of conduct as an aircraft maintenance engineering professional. The aircraft maintenance engineering professionals covered the holder of aircraft maintenance license non type rated category B1 and B2 registered as engineering technician, category B1 and B2 with type rating who is registered as engineering technologist and category C with type rating who is registered as graduate engineer at Board of Engineers Malaysia. Literatures were reviewed and reference to existing professional pathway practices of Engineering Council, United Kingdom through its licensed society such as Royal Aeronautical Society, United Kingdom was an example analyzed. This paper resulted in the proposal of professional development pathway for the CAAM AML holders who are registered at BEM various categories. This paper also clarifies that airworthiness certification of the CAAM AML holders are governed by CAAM. Professional registration of the CAAM AML holder at BEM ensures AML holders complies with the professional code of conduct and ethics as registered engineering professional such as professional engineer (P.Eng). It also ensure continuous professional development as BEM registered engineering personnel. The outcome shows that AML holder professional registration at BEM enhances the AML holder professional development and complement CAAM functions in achieving the Malaysian aerospace blueprint 2030 effectively.